2015
DOI: 10.1016/j.ijpsycho.2014.06.010
|View full text |Cite
|
Sign up to set email alerts
|

The role of temporal structure in the investigation of sensory memory, auditory scene analysis, and speech perception: A healthy-aging perspective

Abstract: Listening situations with multiple talkers or background noise are common in everyday communication and are particularly demanding for older adults. Here we review current research on auditory perception in aging individuals in order to gain insights into the challenges of listening under noisy conditions. Informationally rich temporal structure in auditory signals - over a range of time scales from milliseconds to seconds - renders temporal processing central to perception in the auditory domain. We discuss t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
15
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 142 publications
(201 reference statements)
1
15
0
Order By: Relevance
“…Although in everyday life we can reliably follow one speech stream in a noisy multi-talker environment [1], understanding the brain’s machinery underlying this feat is one of the major challenges of auditory neuroscience. This is due to the fact that solving this problem involves complex functions, such as auditory scene analysis [2], speech processing on multiple timescales [3], and selective attention [48]. Previous neuroimaging data showed a distributed network of brain regions subserving the above functions (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although in everyday life we can reliably follow one speech stream in a noisy multi-talker environment [1], understanding the brain’s machinery underlying this feat is one of the major challenges of auditory neuroscience. This is due to the fact that solving this problem involves complex functions, such as auditory scene analysis [2], speech processing on multiple timescales [3], and selective attention [48]. Previous neuroimaging data showed a distributed network of brain regions subserving the above functions (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Attentional modulation of the delta- and theta-band EEG signal (below ∼7 Hz) has been suggested to reflect a general mechanism of sensory information selection, which is based on temporal expectations[3537]. Some recent studies delivering continuous quasi-naturalistic speech stimuli to listeners provided evidence suggesting that slow oscillatory phase-entrainment mechanisms may be responsible for both the selection and suppression of speech streams in the brain[48]. For instance, delta-theta responses in the posterior temporal lobe are enhanced for the attended but suppressed for the unattended speaker [5].…”
Section: Introductionmentioning
confidence: 99%
“…Rimmele et al ( 2012 ) measured MMN responses to brief two-tone sequences and found reduced MMN amplitude for older adults, indicative of reduced sensory memory with increasing age for auditory temporal order processing. This reflects a more automatic processing of the temporal structure in sensory memory (Näätänen et al, 2010 ) that does not involve explicit memory or attention related deficits at higher levels of processing (Rimmele et al, 2015 ). Indeed, reduced MMN response at rapid rates (i.e., short ISIs) is a robust feature of aging (reviewed by Cheng et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…The use of the app allows large-scale powerful studies to examine the effect of demographic variables such as age [ 24 ] and hearing loss on figure-ground analysis. The present study represents a proof of concept in which we demonstrate that behavior measured via the smartphone app is consistent with our previous psychophysics results [ 15 ].…”
Section: Introductionmentioning
confidence: 99%